2011
DOI: 10.2500/aap.2011.32.3419
|View full text |Cite
|
Sign up to set email alerts
|

Utility of nitric oxide for the diagnosis of asthma in an allergy clinic population

Abstract: Fractionated exhaled nitric oxide (FeNO) expression is increased in airway inflammation and several studies have suggested that FeNO measurement can be useful in patients with asthma. Atopic individuals have increased FeNO levels, indicating that atopy may be a codeterminant in FeNO production. The aim of this study was to determine the discriminative value of FeNO for asthma and other atopic conditions in the general allergy clinic. Patients referred to the outpatient allergy clinic were screened. A standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 0 publications
2
45
1
Order By: Relevance
“…A further three studies 80,81,92 were identified from the update search. Four of these studies 70,77,87,95 included data for FeNO testing in conjunction with another test.…”
Section: Diagnostic Reviewmentioning
confidence: 99%
“…A further three studies 80,81,92 were identified from the update search. Four of these studies 70,77,87,95 included data for FeNO testing in conjunction with another test.…”
Section: Diagnostic Reviewmentioning
confidence: 99%
“…32,33 We carefully noted that, in many of the clinical studies in adults, it is advised to perform F ENO measurements before any other lung function measurement and even before usage of short-acting ␤ 2 agonists, 34,35 and the same order of measurements and procedures is followed by most of the studies in children. 19,20,36 It does not seem justified in the context of our results in children with asthma. Therefore, our results reveal important new clinical aspects regarding the order of measurements in children with asthma.…”
Section: Discussionmentioning
confidence: 52%
“…Moreover, it showed that an increased F ENO level was positively correlated with the presence of respiratory symptoms and air flow reversibility; however, in their study, all subjects were steroid naive. 19 We conducted a similar analysis, and we found a linear increasing trend of change from baseline in bronchial reversibility test using FEV 1 values across 4 F ENO categories of children with moderate asthma. In contrast with our study, in the study by Cordeiro et al, 19 the patients were not categorized into different asthma groups nor was the exact number of participants provided.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations